Refining the dermatological spectrum in primary immunodeficiency: mucosa‐associated lymphoid tissue lymphoma translocation protein 1 deficiency mimicking Netherton/Omenn syndromes. (21st July 2019) - Wiegmann, H.; Reunert, J.; Metze, D.; Marquardt, T.; Engel, T.; Kunde, V.; Ehl, S.; Foell, D.; van den Heuvel, I.; Oji, V.; Wittkowski, H.
Summary: The proteinase mucosa‐associated lymphoid tissue lymphoma translocation protein 1 (MALT1), which forms part of the caspase recruitment domain‐containing protein 11–B‐cell lymphoma 10–MALT1 signalosome complex, plays a direct role in nuclear factor kappa B activation. Here, we describe the case of a female infant with severe immune dysregulation leading to recurrent systemic infections, failure to thrive and severe crises of ichthyosiform erythroderma with high levels of serum IgE. Hence, initial symptoms indicated Netherton syndrome or Omenn syndrome. Surprisingly, sequence analyses of SPINK5 and RAG1/RAG2, respectively, excluded these diseases. During the hospital stay the patient's health deteriorated, despite intensive care therapy, and she died. In order to delineate the diagnosis, whole‐exome sequencing was performed. Two compound heterozygous mutations in MALT1 were found and verified by Sanger sequencing (exon 2 c.245T>C, exon 2 c.310dup), which led to a MALT1 deficiency at the protein level. Based on these results, an immunological analysis was performed, as was immunofluorescence staining of key skin proteins, to confirm a diagnosis of MALT1 deficiency. This case report provides a closer description of the clinical and histological skin phenotype of MALT1 deficiency, and we conclude that MALT1 deficiency must be considered a possible differential diagnosis of Netherton and Omenn syndromes. What's already known about this topic? Mucosa‐associated lymphoid tissue lymphoma translocation protein 1 (MALT1) deficiency is a combined immunodeficiency. MALT1 is part of the caspase recruitment domain‐containing protein 11–B‐cell lymphoma 10–MALT1 signalosome complex, which is essential for nuclear factor kappa B activation. Current publications describe a phenotype of recurrent systemic infections; only in a few cases has an inflammatory involvement of the integument been described. What does this study add? A closer description of the cutaneous phenotype of MALT1 deficiency in a patient with two novel MALT1 mutations. Immune mapping of follicular epidermis shows lympho‐epithelial Kazal‐type‐related inhibitor is reduced in MALT1 deficiency and absent on interfollicular staining. Clinically, MALT1 deficiency mimics Netherton syndrome and Omenn syndrome, and should be considered a differential diagnosis